Fit, Female or Fifty - is cardiac rehabilitation fit for purpose? A systematic review and meta-analysis with meta-regression. (11th May 2021) - Smith, M; Orchard, JJ; La Gerche, A; Gallagher, R; Fitzpatrick, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cardiac rehabilitation (CR) is a multi-disciplinary, evidence-based intervention, aimed to address modifiable risk factors for coronary artery disease. It is recommended worldwide for patients following myocardial infarction (MI), Percutaneous Coronary Intervention (PCI) and cardiac surgery. A growing body of evidence points towards a lack of uptake in CR in females and younger people. Purpose: To examine the effectiveness of contemporary CR programs and assess whether they cater for all patients regardless of age, gender and prior level of fitness, via systematic review, meta-analysis and meta-regression. Methods: MEDLINE was examined for studies involving exercise prescription or CR following MI, PCI and cardiac surgery from January 2010 to May 2020. RCTs and cohort studies of ≥10 patients were included for programs delivering phase II or III CR. Primary outcome measures were peakVO2max, 6-minute walk test (6MWT) and Metabolic Equivalent of Task (METs). Data were extracted using random effects meta-analysis. Epidemiological data were analysed for age, proportion of males to females and prior level of fitness. Baseline level of fitness was assessed by peakVO2max, 6MWT and METs values on entry into CR programs. Meta-regression was then used to determine change in fitness and the influence of age or gender. Results: Thirty-three of the 713 studies (13 RCT, 20 cohort) were eligible and included in the review. Participants had a mean age of 60.0 years and 6/49 (12%) of study groups had a mean age <55 years. Male participants comprised 81.9% of those who completed CR and 41/58 (71%) participants were below average for cardiorespiratory fitness (CRF) when compared to normative values for those aged 60-69 years on entering CR. CRF improved in all study groups by the end of CR programs (mean improvement in peakVO2 3.3mL/kg/min, 6MWT 90.8m and METs 1.7). Meta-regression analysis showed that males were more likely to have an increase in 6MWT distance compared to females (mean difference 3.16m (95% CI 0.44-5.89). However, gender and age did not independently affect peakVO2max or METs. Conclusion: CR following MI, PCI or cardiac surgery improved mean CRF in all study groups. While males were more likely to show an improvement in 6MWT there was no appreciable difference in effect in other outcomes after controlling for age or gender differences. Females, younger people and those of average or above CRF appear to be under-represented in data and attendance at cardiac rehabilitation. Given that CR outcomes are equal across gender and age, more effort should be made to encourage female and younger patients to attend. A 'Precision Medicine' model of exercise prescription may assist in this aim.